PROBLEM BASED LEARNING THROUGH CANVA INTERACTIVE VIDEO: IMPROVING LEARNING OUTCOMES PROBLEM SOLVING IN MATHEMATICS ELEMENTARY SCHOOL TIME MEASUREMENT MATERIALS - Meysa Dewi Adellia Putri; Rusnilawati Rusnilawati (Jurnal Cakrawala Pendas, 2025)
Technological developments encourage innovation in learning models to improve student learning outcomes. The use of technology facilitates the delivery of material and creates a more interesting learning experience. This study aims to examine the application of the Problem Based Learning model combined with Canva interactive video on the learning outcomes of second grade students of Gemarang Elementary School on the subject of measuring mathematical time. This study uses a quantitative approach with a quasi-experimental design, using a pre-test and post-test. The sample of this study consisted of two classes, namely the experimental class at SDN Gemarang (N=23) using the Problem Based Learning model accompanied by Canva interactive videos and the control class at SDN Ngale (N=23) using a contextual model with concrete media. Data analysis techniques included independent t-test, dependent t-test, and N-gain test. The results of the study showed that the use of the Problem Based Learning model with Canva interactive videos effectively improved student learning outcomes. This was proven by the N-gain of the experimental class of 60.37 (medium category), higher than the control class which was only 30.57 (low category). Canva interactive videos support the early stages of Problem Based Learning by presenting problems in an interesting way and helping students develop problem-solving strategies.